PEMBUATAN SABUN CAIR ANTISEPTIK DARI KOMBINASI VIRGIN COCONUT OIL (VCO) DAN TEH HIJAU (Camellia Sinensis) INFUSED OIL: PEMBUATAN SABUN CAIR ANTISEPTIK DARI KOMBINASI VIRGIN COCONUT OIL (VCO) DAN TEH HIJAU (Camellia Sinensis) INFUSED OIL (STIKes Mitra Keluarga, 2022)
The use of synthetic materials as active ingredients in soap making has a negative effect on human skin such as causing irritation. These potential hazards can be overcome by making soap using natural ingredients as activeingredients such as VCO and green tea. The purpose of this activity is to provide socialization to the community in the Pasir Jambak Coast of Padang regarding Hand Washing with Soap (CTPS). In technical implementation, thecommunity service team made liquid soap followed by education about CTPS and the distribution of free liquid soap to the community. The implementation methods and approaches developed in the PKM program activities can overcome the mindset about the importance of washing hands. The result of this service is that the community is enthusiastic in participating in counseling and understanding the importance of CTPS.